PENINGKATAN HASIL BELAJAR GERAK DASAR TOLAK PELURU GAYA ORTODOKS MELALUI PENDEKATAN BERMAIN â€œRISHOâ€ PADA SISWA KELAS IV SDN JRAGUNG 2 KECAMATAN KARANGAWEN KABUPATEN DEMAK TAHUN PELAJARAN 2012 / 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to improve the learning outcomes of basic motion through the shot-put styleunorthodox approach to playing